What do humpback whales Megaptera novaeangliae (Cetartiodactyla: Balaenopteridae) pairs do after tagging? - Artur Andriolo; Alexandre N. Zerbini; Sergio Moreira; José L. Pizzorno; Daniel Danilewicz; Ygor G. Maia; Natália Mamede; Franciele R. de Castro; Phillip Clapham (Zoologia (Curitiba), 2014)
The social structure of humpback whales in their tropical wintering grounds is very fluid. To date, no information has been published for cases in which two whales were both satellite-tagged while in association. Here, we report the movements of four humpback whale pairs tagged together off the coast of Brazil. Fieldwork and satellite tagging of humpback whales was conducted between 2003 and 2008 along the eastern coast of Brazil, between 20°S and 8°S. Movement was monitored while whales were still in their breeding ground. A switching state space model was applied to the filtered data of each humpback whale to standardize telemetry data and allow direct comparison of each individual track. GIS was used to plot model-predicted locations and to visually compare animal movements. The results confirm the short-lived nature of associations between breeding humpback whales, and shows that individuals differ widely in their movements.